2017
DOI: 10.1002/casp.2298
|View full text |Cite
|
Sign up to set email alerts
|

The Humanisation of Refugees: A Discourse Analysis of UK Parliamentary Debates on the European Refugee ‘Crisis’

Abstract: Previous research has explored the 'othering' and dehumanisation of asylum seekers and refugees, yet comparatively little research has explored the opposite process: the humanisation of refugees. This article applies discursive psychological analysis to the transcripts of five UK Parliamentary debates on the European refugee 'crisis' from September 2015 to January 2016, examining an explicit form of humanisation: categorising refugees as 'human beings'. The analysis focuses on the nature and function of such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 29 publications
0
55
0
2
Order By: Relevance
“…Similarly to what we saw in the Finnish rhetoric above, during the beginning of autumn 2015 talk of humanism and solidarity dominated the discourse of the Swedish PM (see also Kirkwood, ; Nightingale et al, ; Sambaraju et al, ). Löfvén emphasized that receiving and helping refugees in need, people who are fleeing for their lives, is a moral responsibility of the entire Swedish nation.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Similarly to what we saw in the Finnish rhetoric above, during the beginning of autumn 2015 talk of humanism and solidarity dominated the discourse of the Swedish PM (see also Kirkwood, ; Nightingale et al, ; Sambaraju et al, ). Löfvén emphasized that receiving and helping refugees in need, people who are fleeing for their lives, is a moral responsibility of the entire Swedish nation.…”
Section: Discussionmentioning
confidence: 54%
“…This news, reported both nationally and internationally, shows how Sipilä manages his stake and interest as PM and constructs for himself a “subject position of a humane and solidary helper.” The announcement appeared only 3 days after the heart‐breaking pictures of 3‐year‐old Alan al‐Kurdi were distributed in the media and can, thus, also be considered as a response to this, as illustrated in Extract below (cf. Goodman et al, ; Kirkwood, ; see also the Swedish PM's rhetoric in Extract below).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it has been demonstrated that arguments based on these did appear to be made regarding the wider refugee crisis, especially following the photographs of a drowned 3year-old refugee (Goodman et al, 2017), and that these humanitarian arguments are some of the strongest pro-refugee strategies (Kirkwood, 2017;Wroe, 2018), these arguments are generally missing from this particular discussion and are not found to be used to respond to some of the anti-asylum arguments that are featured in this analysis. Of particular note is the lack of arguments based on compassion and/or humanitarianism throughout the debate.…”
Section: Discussionmentioning
confidence: 85%